Analysis of the Sand Drying Process in the Biomass-Energized Rotary Drying Machine: Analysis of the Sand During Process in the Biomass-Energized Rotary Drying Machine - Susanto, Herry; Setyobudi, Roy Hendroko; Faturachman, Danny; Yandri, Erkata; Priyatna, Asep Hendiarko; Daryus, Asyari; Gaile, Zane Vincevica; Wahono, Satriyo Krido; Mahaswa, Rangga Kala; Mel, Maizirwan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Hebel brick (also known as a lightweight brick) is a product of modern building materials because it has a lighter weight but it is stronger than cement bricks and red bricks. Hebel bricks can withstand pressures of more than 4 MPa and are suitable as building wall materials, and speed up construction, and save on cement material costs. One of the most important materials is silica sand in the manufacture of Hebel bricks. The silica sand used in the manufacture of Hebel bricks must have a moisture content of 10 % to 15 %. The purpose of this study is to provide a solution in the form of a drying technique design using a rotational speed control method and a machine that uses biomass-based energy sources. This rotary drying machine is designed to be able to dry wet silica sand into silica sand with water content according to standards. The development of this drying machine begins with making an initial design and parameter analysis. Then proceed to the design, manufacture, and performance testing. The calculation results show that the wet base moisture content has decreased from 33.17 % to 16.58 %, the dry base moisture content decreased from 49.63 % to 19.88 % and drying efficiency also decreased from 63.11 % to 17.11 %. Hence it can be seen that the percentage of wet base moisture content reduced by 50 %, the percentage of dry base moisture content reduced by 59.94 %, and the percentage of drying efficiency reduced by 72.9 %.